Organic amendments tighten nitrogen cycling in agricultural soils: a meta-analysis on gross nitrogen flux - Breza, Lauren C.; Grandy, A. Stuart (Frontiers in Agronomy, 2025)
IntroductionUnderstanding how nutrient inputs affect nitrogen (N) transformations and storage is vital for developing sustainable agroecosystems. Organic N inputs, such as crop residues (e.g., cover crop biomass and stover) and animal manures, can accelerate N cycling by increasing mineralization and immobilization rates to provide crops with more opportunities to intercept N as it moves through bioavailable pools. We aimed to understand how organic and synthetic soil amendments inhibit or promote N mineralization, immobilization, and nitrification rates.MethodsWe conducted a meta-analysis of peer-reviewed studies to assess N transformation rates in agroecosystems. Specifically, we targeted studies employing 15N pool dilution methods to quantify N mineralization, immobilization, and nitrification rates in response to organic and synthetic soil amendments.Results and discussionOur findings indicate that adding synthetic, manure, and crop derived residues as soil amendments increased mineralization by 60%, 135%, and 214%, respectively, relative to the unamended controls. While manure and residue produced similar mineralization rates, residue amendments induced significantly higher immobilization rates than synthetic and manure amendments – a sevenfold and fourfold increase, respectively. Furthermore, only residue N amendments enhanced the ammonium (NH4+) pool size, while synthetic and manure amendments resulted in no change in NH4+ pool size. These results suggest that residue amendments encourage tighter coupling of the carbon (C) and N cycles compared to manure or synthetic amendments by delivering C rich substrates (e.g., C:N ratio >20:1) to soil microbes. This tighter coupling with residue amendments leads to faster mineralization-immobilization processes and larger NH4+ pools than those observed with manure or synthetic amendments. As such, residue amendments encourage soil N recycling between inorganic and organic forms, which is crucial to supporting crop N needs throughout the growing season while minimizing N losses.